Keanekaragaman Jenis Mangrove di Desa Rukam Kabupaten Bangka Barat - Dwi Rosalina; Dini Sofarini (Universitas Lambung Mangkurat, 2021)
Research on mangrove species diversity has been carried out in Rukam Village, West Bangka Regency. This study aims to determine the diversity of mangrove species in Rukam Village, West Bangka Regency. This research was conducted using purposive sampling at five research stations. Transects are drawn perpendicular to the coastline starting from the outermost vegetation (near the sea) to the final boundary of the littoral area (land). The results obtained were the diversity index was classified as low ranging from 0.4 - 0.74, the uniformity index value was evenly distributed between 0.57 - 0.97 and the dominance index value ranged from 0.2 - 0.5, there were types that dominated. other types, so that the community structure is unstable and there is ecological stress.